Thought, Kabbalah, and Religious Polemics in Medieval Hispanic-Hebrew Judaism. A Bibliographical Approach - Sainz de la Maza, Carlos N.; Alba Cecilia, Amparo ('Ilu. Revista de Ciencias de las Religiones, 2007)
Sin resumen